2004
DOI: 10.1161/01.str.0000117574.19517.80
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Cost-Effectiveness of Stroke Units in France Compared With Conventional Care

Abstract: Background and Purpose-The incidence of stroke in France is estimated at between 120 000 and 150 000 cases per year.This modeling study assessed the clinical and economic benefits of establishing specialized stroke units compared with conventional care. Methods-Data from the Dijon stroke registry were used to determine healthcare trajectories according to the degree of autonomy and organization of patient care. The relative risks of death or institutionalization or death or dependence after passage through a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 16 publications
2
42
0
4
Order By: Relevance
“…10 -12 Existing studies suggest that SU care is more expensive than the alternatives and there is only one study on the cost-effectiveness of SUs, which suggests that such increased costs are justified by the improved outcomes and this results in favorable incremental cost-effectiveness ratios for SU care. 12 Despite the recorded benefits of SUs dealing with acute treatment, there is less conclusive information available on the effective management of discharge and follow-up after acute SU care. The Royal College of Physicians Stroke guidelines state that "Specialist stroke services should be available in the community as a part of an integrated system of care to facilitate early supported discharge."…”
mentioning
confidence: 99%
“…10 -12 Existing studies suggest that SU care is more expensive than the alternatives and there is only one study on the cost-effectiveness of SUs, which suggests that such increased costs are justified by the improved outcomes and this results in favorable incremental cost-effectiveness ratios for SU care. 12 Despite the recorded benefits of SUs dealing with acute treatment, there is less conclusive information available on the effective management of discharge and follow-up after acute SU care. The Royal College of Physicians Stroke guidelines state that "Specialist stroke services should be available in the community as a part of an integrated system of care to facilitate early supported discharge."…”
mentioning
confidence: 99%
“…Over the five-year period, however, stroke unit care increased survival with only minor disability by 240 days, yielding an incremental cost-effectiveness ratio associated with stroke care of just €1,359 per year of life gained with only minor disability. 45 The following assumptions were made in modeling the effect of this element of optimal care:  The 20% reduction in death and dependency reflects patients that would instead be discharged home  A maximum of 80% of stroke patients would be treated in an organized stroke unit, given the likelihood that smaller hospitals may not be in a position to establish organized stroke units and that not all stroke patients would be transferred to a hospital with an organized stroke unit. The effect of this assumption will be tested via sensitivity analysis.…”
Section: 42mentioning
confidence: 99%
“…3 More recent studies have generated additional data supporting the efficacy and costeffectiveness of stroke units. 215,216 A recent study found that stroke patients cared for in a stroke unit with continuous cardiac telemetry monitoring were more likely to have significant cardiac arrhythmias detected compared with stroke unit patients who did not have such monitoring. 217 This observation is shared by many vascular neurologists.…”
Section: Stroke Unit and Icumentioning
confidence: 99%